Spontaneous jaw muscle activity in patients with acquired brain injuries—Preliminary findings. Issue 2 (April 2018) - Kothari, Mohit; Madsen, Vibeke Louise Funch; Castrillon, Eduardo E.; Nielsen, Jørgen Feldbæk; Svensson, Peter
Abstract: Patients: High or excessive parafunctional jaw muscle activity is a frequent complication of acquired brain injury (ABI) and may have some similarities to bruxism. Bruxism has been associated with increased tooth wear, masseter hypertrophy and headaches. The aim of this observational study was to identify the levels of jaw muscle activity from fourteen ABI patients having different functional and cognitive levels in their early phase of neurological rehabilitation (according to their Ranchos Los Amigos Scale (RLAS) score). Nine patients were severely cognitive impairement (RLAS score 1–3): with no or little response to any external stimuli due to low arousal and five patients were with RLAS score 4–8: depending on responses to stimuli and confusion level i.e. defining that patients had enough arousal to respond and react and therefore were able to follow the instructions. A single-channel electromyographic (EMG) device was used to assess the jaw muscle EMG activity in ABI patients for two hours continuously at two different days. Discussion: The mean (± SD) jaw muscle activity observed in patients with ABI was 46.9 ± 6.5 EMG events/h with a wide range between 1–163 EMG events/h but with no significant difference between days (P = 0.230). Conclusion: Irrespective of functional and cognitive ability scores patients with ABI had a wide range of EMG activity. The use of ambulatory single-channel EMG devices might open a path for further studies to determine levels of jaw muscle activity associated with potential side effects in ABI patients.